Women of the great barrier reef: Stories of gender and conservation - Foxwell-Norton, Kerrie; Anderson, Deb; Leitch, Anne M. (Queensland Review, 2021)
In the late 1970s, Carden Wallace was at the beginning of her lifelong exploration of the Great Barrier Reef - and indeed, reefs all over the world. For Wallace, who is now Emeritus Principal Scientist at Queensland Museum, the beginning of her Reef career coincided with the emergence of both feminist and environmental movements that meant her personal and professional lives would be entwined with a changing social, cultural and political milieu. In this article, we couple the story of Wallace's personal life and her arrival in coral science to identify the Reef as a gendered space ripe to explore both feminist and conservation politics. The article is part of a broader Women of the Reef project that supports a history of women's contribution to the care and conservation of the Reef since the 1960s. In amplifying the role of women in the story of the Reef, we find hope in the richness of detail offered by oral history to illuminate the ways discourse on the Reef and its women sits at the intersection of biography, culture, politics and place. In these stories, we recognise women's participation and leadership as critical to past challenges, and to current and future climate change action. By retelling modern Reef history through the experiences and achievements of women, we can develop new understandings of the Reef that disrupt the existing dominance of patriarchal and Western systems of knowledge and power that have led us to the brink of ecological collapse. © The Author(s), 2022.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; approches et analyses; australie; changements climatiques; environnement; histoire et politique; océanie; patriarcat; projet charge mentale; périodes historiques; régions géographiques; rôle des femmes dans la protection de la grande barrière de corail; systèmes d'oppressions; thématiques

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences